Color atlas of histology - Gartner, Leslie P; Hiatt, James L (Williams & Wilkins, 1990)
This atlas of histology is aimed at medical, dental and allied health students for use in the laboratory, as well as to give assistance for practical and didactic exams. Each chapter begins with a discussion of the structure and function of the tissue or organ system and ends with a functional summary, which allows students to see the connection between the anatomy and physiology of the subject matter presented in the chapter. Photomicrographs are arranged from low power overviews to higher magnifications. New to this edition are key terms in bold and a two-page spread of 3D artwork with accompanying narrative in each chapter, which should bring an added dimension to parts of the body students are viewing in a single dimension under the microscope.
Keywords: Histology; histologie